Physical Activities Decrease Fasting Blood Glucose Level in Diabetes Mellitus Type 2 Patients: Use of International Physical Activity Questionnaire (IPAQ) in Rural Area (Majalah Kedokteran Bandung, 2019)
An increase in the incidence of diabetes mellitus type 2 (DM-2) has been observed from 1.1% in 2007 to 1.5% in 2018 with incidents occur in both urban areas and rural areas of Indonesia. Garut as one of the rural areas in Indonesia is the fourth district with the highest DM-2 incidence in West Java Province, Idnonesia. Physical activity is considered to affect the glycemic control and weight loss in DM-2 patients. Therefore, the purpose of this study was to determine the relation between the physical activity level and blood glucose level in DM-2 patients in Garut, Indonesia. This was a cross-sectional observational analytic study on 46 DM-2 patients who were the members of the Garut Branch of the Indonesian Diabetes Association (PERSADIA), in May 2018. The physical activity level was measured using the International Physical Activity Questionnaire (IPAQ) while the blood glucose level was measured using fasting blood glucose level test. Data were then analyzed using analysis of variance test. Results showed that most participants had a low level of physical activity (52.2%) while the lowest fasting blood glucose was obtained from patients with high physical activity (98.63±11.6), compared to those with moderate and low physical activity levels (123.43±20.16 and 164.21±19.04 mg/dL, respectively) with p=0.000 (p
Keywords: Diabetes mellitus type 2; fasting blood glucose level; IPAQ; physical activity; rural area